The riddle of Timaeus - Grzybowski, Juliusz (Hybris, 2016)
This article focuses around the riddle, which Timaeus asks Socrates. I will therefore deal with troublesome absence of Socrates in troublesome dialogue of Plato’s. I will deal with a riddle and I will try to remember that the riddle is deadly dangerous, at least for those who deal with wisdom, and therefore perhaps especially for philosophers. I will evoke the fragment B 56 of Heraclitus, where we can hear the story about Homer’s death. Briefly: I will be wondering why Socrates is not dead after hearing riddle of Timaeus.